2016
DOI: 10.5152/tud.2016.78700
|View full text |Cite
|
Sign up to set email alerts
|

Does length of prostate biopsy cores have an impact on diagnosis of prostate cancer?

Abstract: Objective: To investigate whether core length is a significant biopsy parameter in the detection of prostate cancer. Material and methods:We retrospectively analyzed pathology reports of the specimens of 188 patients diagnosed with prostate cancer who had undergone initial transrectal ultrasound (TRUS) guided prostate biopsy, and compared biopsy core lengths of the patients with, and without prostate cancer. The biopsy specimens of prostate cancer patients were divided into 3 groups according to core length, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Achieving adequate core length is crucial for the diagnosis of cancer. In two recent retrospective studies of over 2000 biopsies each, the average biopsy length was between 11.3 and 13.3 mm [11,12]. In a study of over 17,000 biopsies the average length was 10.44 ± 2.36 mm [13].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving adequate core length is crucial for the diagnosis of cancer. In two recent retrospective studies of over 2000 biopsies each, the average biopsy length was between 11.3 and 13.3 mm [11,12]. In a study of over 17,000 biopsies the average length was 10.44 ± 2.36 mm [13].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since the biopsy core length determines the quality of a specimen and given the impact of core length on cancer detection [ 25 ], we considered only the biopsy samples with a suitable length (i.e., 12 mm) and observed that our ratios worked regardless of the length of biopsy specimen, being the only predictors of Gleason score agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included patients with a history of neoadjuvant hormonal therapy or chemoradiotherapy before RP surgery, active surveillance, previous surgery for benign prostatic hyperplasia (BPH), a core length less than 12 mm [ 25 ] and those patients who had incomplete medical records. Clinical and pathological data were recorded for all patients and bx-GSs were compared with their surgical counterparts.…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies have been published on the number and localization of the cores in the literature, very few have investigated the effect of core length as an indicator of the quality of prostate biopsy (13). This may be affected by many factors, including the length of the core obtained in a biopsy, the biopsy technique performed by the urologist, the diameter of the biopsy needle, the rigidity of the site the sample obtained, and the method of sample collection (14).…”
Section: Discussionmentioning
confidence: 99%